The Distortion Theorems for Harmonic Mappings with Negative Coefficient Analytic Parts (Journal of Mathematical Study, 2018)
Some sharp estimates for coefficients, distortion and the growth order areobtained for harmonic mappings $f \in TL^{α}_H,$ which are locally univalent harmonic mappingsin the unit disk $\mathbb{D}:=\{z:|z|